The effect of prematurity on visual perceptual skills amongst School-age children in grade 4-6 at Pulamadibogo School in Mankweng, Limpopo Province - Mmusi-Landela, Lerato Khensani (My University, 2018)
Children born preterm and low birth weight may have long-term negative consequences for visual function, compared with children born at full term. Visual memory (sensory), perceptual skills and learning are of fundamental importance for a range of functions and everyday activities, such as normal classroom learning, school performance and social interactions and may contribute to academic difficulties.The purpose of this study was to investigate the effect of gestational age and birth weight on visual perceptual skills.The study was approved by the University of Limpopo, Turfloop Research Ethics Committee. The Department of Education, Limpopo Province granted permission to conduct the study. Written informed consent was obtained from parents of the children and the study adhered to the tenets of the Helsinki Declaration.
Thesis (MPH.) -- University of Limpopo, 2018
Keywords: Birth weight; Preterm; Visual perception; TVPS-3; Visual perception; Gestational age; Birth weight; Public health